Assessment of genetic diversity for salinity tolerance in Indian mustard using SSR markers (Journal of Oilseed Brassica, 2025)
Salinity presents a major challenge for Indian mustard cultivation, especially during the seedling stage in salt-affected soils. Developing salt-tolerant mustard lines through targeted breeding, supported by germplasm screening and genetic variability assessment, can enable cultivation in these areas. This study aimed to evaluate salinity tolerance and assess genetic diversity among 48 Indian mustard genotypes under greenhouse conditions at the seedling stage, exposed to control, 8 dSm-1, and 12 dSm-1 salinity stress levels. Molecular diversity was analysed using 59 SSR primers, of which 24 polymorphic primers produced 48 distinct alleles. The mean polymorphism information content (PIC) was 0.40, with a gene diversity of 0.49. Based on Jaccard’s dissimilarity coefficients, the genotypes clustered into two main groups. These SSR markers hold potential for marker-assisted selection, and the genetically diverse genotypes identified can serve as valuable parents in breeding programs aimed at enhancing salt tolerance and yield in Indian mustard. Overall, the identified genetic diversity and promising salt tolerant germplasm provide a foundation for developing salt-tolerant cultivars in Indian mustard breeding efforts.